Learning design of lines and angles for 7th -grade using Joglo traditional house context - Hartono, Hartono; Nursyahidah, Farida; Kusumaningsih, Widya (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2021)
Lines and angles are essential for students because of geometry and its many applications in daily life. However, there are still many students who have difficulty grasping the material. Therefore, it is necessary to design learning using the right approach, context, and media. This study aims to produce a learning trajectory that can assist students in understanding the concept of lines and angles, maximize the effectiveness and efficiency of learning, create meaningful learning, and motivate student learning. This study used the Joglo Traditional House context as a starting point and the design research method developed by Gravemeijer and Cobb with three main steps: preparing for the experiment, designing the experiment (pilot experiment and teaching experiment), and retrospective analysis. However, in design experiment step is limited to the pilot experiment. In this study, all activities were designed based on Indonesian Realistic Mathematics Education. It involves six 7th-grade students from one of the junior high schools at Juwana Resident with three different abilities, namely two students for each level with high, moderate, and low ability. The learning trajectory generated in this study consists of a series of learning processes in four activities that can be used to develop local instructional theories and develop designs for further activities. Those are observing Joglo traditional house video for understanding lines and angles concepts, deducing line positions, discovering the angles' properties on parallel lines intersected by other lines, and solving lines and angles problems.